Investigation on the static fatigue mechanism and effect of specimen thickness on the static fatigue lifetime in WC–Co cemented carbides - Ding Chen; Liang Yao; Zhenhua Chen; Huiping Wang; Wen Peng (Сверхтвердые материалы, 2018)
The static fatigue mechanism and effect of specimen thickness on static fatigue lifetime for four WC–Co cemented carbides were studied with different binder contents and carbide grain sizes. Static fatigue tests under three-point bend loading were conducted on different sized specimens. The fracture surfaces of rupture specimens were examined by scanning electron microscopy to investigate the static fatigue micromechanisms. Досліджено механізм статичної втоми і вплив товщини зразка на термін служби при статичній втомі для чотирьох твердих сплавів WC–Co з різним вмістом зв’язки і розміром зерен. Випробування на статичну втому при навантаженні за схемою триточкового вигину було проведено на зразках різних розмірів. Поверхні зламів зруйнованих зразків було вивчено c допомогою скануючої електронної мікроскопії з метою дослідження мікромеханізму статичної втоми. Исследованы механизм статической усталости и влияние толщины образца на срок службы при статической усталости для четырех твердых сплавов WC–Co с различным содержанием связующего и размером зерен. Испытания на статическую усталость при нагрузке по схеме трехточечного изгиба были проведены на образцах различных размеров. Поверхности изломов разрушенных образцов были изучены c помощью сканирующей электронной микроскопии с целью исследования микромеханизмов статической усталости.